The taxonomic study of the Malpighiaceae Juss. family of the restingas of Algodoal/Maiandeua, Maracanã, Pará, Brazil - Alexandrino, Vitor Hugo Dias; Sousa, Julio dos Santos de; Bastos, Maria de Nazaré do Carmo (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2011)
This study deals with the taxonomic treatment of species of the Malpighiaceae Juss. occurring in the Environmental Protection Area (APA) Algodoal/Maiandeua, Maracanã, Pará. The methodology includes the analysis of botanical material originated from new collections and specimens of the herbaria of the Museum Goeldi (MG) and of the Agronomic Institute of the North (IAN), beyond specialized literature. There are five species, distributed across three genera Malpighiaceae: Banisteriopsis caapi (Spruce ex Griseb.) C.V. Morton., Byrsonima laevis Nied., Byrsonima chrysophylla Kunth, Byrsonima crassifolia (L.) Kunth e Heteropterys nervosa A. Juss. The genus Byrsonima Rich. ex Kunth was the most representative, presenting three species. Byrsonima laevis and Banisteriopsis caapi are new records for the sand coast of Pará. Sandbank forest formation was the ecosystem which had the largest number of species. Identification keys, descriptions, and illustrations of the taxa are presented, as well as data concerning geographical distribution, additional comments and habitat of the taxa.